Deferred CPA: Accountancy Graduates Decision in Taking the CPA Licensure Examination - Quito, Jhaschel B.; Viray, Fritzie Mae V.; Mendoza, Raisha Nicole C.; Saldi, Kurt Aron N.; Lozada, Enrico L.; Castro, Wilden Y.; Akiate, Yuri Walter D. (International Journal of Research in Interdisciplinary Studies, 2023)
Many BSA graduates decide not to take the board exam after graduation for a variety of reasons. This qualitative study was carried out in order to identify the obstacles influencing BSA graduates' decisions about applying for the board exam. Many quantitative studies exist about this study, but only a few were conducted that dug deeper into the reasons affecting the decisions of BSA graduates. This study was conducted on 15 graduates of Bachelor of Science in Accountancy (BSA) who had not yet taken the board exam and graduated in 2022 through purposive sampling. Data were collected by interviewing each individual via Google Meet with two main questions: why they did not take the board exam and what interventions may help them and future BSA graduates. The responses identified financial constraints as the major reason for not taking the board exam. Some answered that having online classes during their college years did not help at all in building their foundation for the board and, some argued that having a title is not needed in their job, so they don’t find taking the board exam reasonable, inadequate basic knowledge, not having the confidence to take the board exam, the complexity of the exam, discouragement from the low passing rate of the exam and not having the motivation to pursue it also affects the decision of the BSA graduates. The findings of this study suggest that the government and the university should assist graduates and future graduates by offering financial assistance and improving their way of learning. The result of this study holds significance for educators, academic institutions, and accreditation bodies.